Treatment of A Traumatic Injury of Hand With Persian Medicine - Kenari, Hoorieh Mohammadi; Kordafshari, Gholamreza; Aghighi, Somayeh; Moghimi, Maryam (Archives of Clinical and Biomedical Research, 2018)
Introduction: Trauma and its complications are one of the most important causes of workforce disability in the community. Therefore, for the more effective treatment of traumatic complications, the use of traditional and complementary medicine capacities along with conventional medicine seems to be necessary. Case Report: The patient was a 44-year-old man under the care of conventional medicine due to a trauma of the right hand. But the treatment was not successful, and eventually the patient was a candidate for amputating four right fingers. Fortunately, therapeutic measures and leech therapy in Persian medicine prevented the fingers from amputation and returned the normal function of the hand to the patient. Conclusion: Persian medicine was successful in treating the patient with a nutritional modification, body reinforcement, body cleansing of waste materials, local clearance of the site of injury, and preventing the re-accumulation of waste materials at the site of injury, along with the early therapies of conventional medicine.